Advances in corneal cell therapy. (September 2016) - Fuest, Matthias; Yam, Gary Hin-Fai; Peh, Gary Swee-Lim; Mehta, Jodhbir S
Corneal integrity is essential for visual function. Transplantation remains the most common treatment option for advanced corneal diseases. A global donor material shortage requires a search for alternative treatments. Different stem cell populations have been induced to express corneal cell characteristics in vitro and in animal models. Yet before their application to humans, scientific and ethical issues need to be solved. The in vitro propagation and implantation of primary corneal cells has been rapidly evolving with clinical practices of limbal epithelium transplantation and a clinical trial for endothelial cells in progress, implying cultivated ocular cells as a promising option for the future. This review reports on the latest developments in primary ocular cell and stem cell research for corneal therapy.